Embodied experiences: affective and cognitive benefits of gaming. Video games, nightmares, and emotional processing - Gackenbach, Jayne; Bown, Johnathan (My University, 2015)
Emotions, Technology, and Digital Games explores the need for people to experience enjoyment, excitement, anxiety, anger, frustration, and many other emotions. The book provides essential information on why it is necessary to have a greater understanding of the power these emotions have on players, and how they affect players during, and after, a game.
Keywords: Electronic games -- Psychological aspects; Electronic games -- Social aspects; Digital media -- Social aspects; Human-computer interaction